2017
DOI: 10.5267/j.ijiec.2016.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Solving machine loading problem of flexible manufacturing systems using a modified discrete firefly algorithm

Abstract: This paper proposes a modified discrete firefly algorithm (DFA) applied to the machine loading problem of the flexible manufacturing systems (FMSs) starting from the mathematical formulation adopted by Swarnkar & Tiwari (2004). The aim of the problem is to identify the optimal jobs sequence that simultaneously maximizes the throughput and minimizes the system unbalance according to given technological constraints (e.g. available tool slots and machining time). The results of the algorithm proposed have been co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…It can be extended as a multi-objective, such as minimizing the makespan and tardiness as they are conflicted. As another future research, the performance of the proposed algorithm can be compared with other heuristic algorithms that were presented in other studies [33].…”
Section: Discussionmentioning
confidence: 99%
“…It can be extended as a multi-objective, such as minimizing the makespan and tardiness as they are conflicted. As another future research, the performance of the proposed algorithm can be compared with other heuristic algorithms that were presented in other studies [33].…”
Section: Discussionmentioning
confidence: 99%
“…The research result showed that significantly savings were realized as compared to a production plan without considering energy consumption. Additional works (Khouja & Mehrez, 1994;Giri & Dohi, 2005b;Sana, 2010;Liu et al, 2017b;Bottani, et al, 2017;Chiu et al, 2018c,d;Ameen et al, 2018) were also conducted to address various issues and influences of variable fabrication rates on manufacturing systems. As little attention has been paid to study the joint influences of stochastic failures, random scrap, and expedited fabrication rate on the manufacturing runtime decision, this work aims to link the gap.…”
Section: Introductionmentioning
confidence: 99%
“…Swarm-based algorithms are popularly used algorithms for solving scheduling problems. Bottani et al [24] developed an efficient heuristic based on firefly algorithm, defined two vectors for each firefly to represent a candidate solution and optimized by the objective function, the aim to formulate an objective function which takes into account both the throughput and the system unbalance, and the results show that the algorithm is feasible. Zhou et al [25] presented a multi-population discrete firefly algorithm and combined with the k-opt algorithm to solve the traveling salesman problem.…”
Section: Introductionmentioning
confidence: 99%